Strategi Bersaing Benih Padi Berlabel Unit Pengembangan Benih Tanaman Pangan dan Hortikultura (UPBTPH) Provinsi Kalimantan Barat - Budihandayani, Emilia Farida; Nurliza, Nurliza; Imelda, Imelda (Jurnal Aplikasi Manajemen, 2016)
Agency for food plantation and horticulture seed development (UPBTPH) in Wes  Kalimantan has faced competetion on industry of labeled rice seed. This research aims in studying on industrial circle and competitive advantages strategies that could be used by UPBTPH in West Kalimantan. Respondents are selected through purposive sampling method. Meanwhile, data analyzed use Delphi Method. Industrial circle described on Porter Model and General Electric Matrix. The analysis result of Porter Model shows that UPBTPH is good on cost leadeship strategy. It means that UPBTPH could be the lowest cost producer. The analysis result of General Electric Matrix shows that UPBTPH as a company on selective growth segmentation. It affects UPBTPH should be more selective in growth segmentation. Therefore the company should: (1) generate on production capacity, (2) keep on management and product standardization, (3) doing well on collaboration with executive for primary seed (UPBS) and an Agency for Controlling and Seeds Certification (BPSB) in West Kalimantan are competitive advantage strategies that suitable for UPBTP